(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2018)
“Where data (state) outlives the process that created it”. Persistence is one of the fundamental concepts in application development. In programming, persistence refers specifically to the ability to retain data structures between program executions, such as, for example, an image editing program or a word processor saving their documents to avoid data loss in the event of power failures. Object Persistency is an Open source Object-relational mapping framework for Java. Versions 3.2 and later provide an implementation for the Java Persistence API. Driven by XML a configuration file to configure data connectivity and map classes to database tables and DAO is thereby used to hide complex ORM. · Java/SQL code generation tools. · Developer writes code to call API. · API executes necessary SQL at runtime. Object Persistency Eliminate need for repetitive SQL. It Work with classes and objects instead of queries and result sets. Handles all create-read-update-delete (CRUD) operations using simple API; no SQL Generates DDL scripts to create DB schema (tables, constraints, sequences). Supports over 20 RDBMS; change the database by tweaking configuration files.